2014
DOI: 10.1039/c3cc47376g
|View full text |Cite
|
Sign up to set email alerts
|

Three component assemblies by orthogonal H-bonding and donor–acceptor charge–transfer interaction

Abstract: Three component supramolecular assemblies from a mixture of an aromatic donor (D), acceptor (A) and external structure directing agent (ESDA) are achieved by orthogonal noncovalent interactions involving two different types of H-bonding and alternate D-A stacking. An ESDA containing amide or urea produces a charge-transfer gel and sol, respectively, owing to their contrasting morphology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 37 publications
(9 reference statements)
1
36
0
Order By: Relevance
“…4 .F ree energies of aggregation( DG 298 in cyclohexane)are + 5.5 kcal mol À1 for 1' and À2.6 kcal mol À1 for 2'. Our results show that the interplay of various types of orthogonal noncovalent interactions is an efficient method to create ordered supramolecular polymers that are stabilized by cooperative effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 .F ree energies of aggregation( DG 298 in cyclohexane)are + 5.5 kcal mol À1 for 1' and À2.6 kcal mol À1 for 2'. Our results show that the interplay of various types of orthogonal noncovalent interactions is an efficient method to create ordered supramolecular polymers that are stabilized by cooperative effects.…”
Section: Discussionmentioning
confidence: 99%
“…[1] The molecular organization correlates with the specific intermoleculari nteractions during the supramolecular polymerization process and is more amenable to detailed research when using one-dimensional systems. [3] The exploitation of cooperative hydrogen bonds based on functional groups such as ureas, [4] bisureas, [5] amides, [6] bisamides, [7] melamines [8] and peptides [9] often reinforced by p-p interactions [10] is aw ell-known strategyt of ine tune the aggregation modes and in turn, the degree of order in theses ystems. [3] The exploitation of cooperative hydrogen bonds based on functional groups such as ureas, [4] bisureas, [5] amides, [6] bisamides, [7] melamines [8] and peptides [9] often reinforced by p-p interactions [10] is aw ell-known strategyt of ine tune the aggregation modes and in turn, the degree of order in theses ystems.…”
Section: Introductionmentioning
confidence: 99%
“…Substantial charge carrier delocalization owes to a long‐range order possessed by such nanocables. However, to improve the conduction pathways in such 1D architectures, many research groups have either relied on doping (I 2 , NH 2 −NH 2 ) or adopting a donor–acceptor charge‐transfer (CT) mixed valence states, compromising their luminogen properties . Single‐component transport active luminogen assemblies are essential for next generation plastic electronics because they can actually simplify and shorten the device fabrication procedure with lesser production cost .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Substantial chargec arrierd elocalization owes to al ong-range order possessed by such nanocables.H owever,t oi mprove the conduction pathways in such 1D architectures, many research groups have either relied on doping (I 2 ,N H 2 ÀNH 2 )o ra dopting ad onor-acceptor charge-transfer (CT) mixed valence states, compromising their luminogen properties. [6][7][8] Single-component transport active luminogen assemblies are essential for next generation plastic electronics because they can actually simplify and shorten the devicef abrication procedure with lesser productionc ost. [9] However,s imultaneousg ain of high transport efficiency and luminescence in single-component assemblies are rarely reported due to difficulty in merging two self-opposing factors, i.e.,1)Strong intermolecular space delocalization( p···p)o fp-electronc loud improves electronic features [10] and 2) On the contrary,s trong face-to-face intermolecular p···p interactions trigger delocalized excitons, rendering the molecular assembly to be non-emissive or fluoresce weakly.…”
Section: Introductionmentioning
confidence: 99%
“…The charge‐transfer band at around λ =570 nm decreased upon addition of 5 % MeOH, and the initial red color of the solution disappeared. Also, in the presence of methanol, the gel turned into solution, indicating the collapse of the hydrogen‐bonded network 8. A comparison of the CT band of the three‐component assembly in CHCl 3 and gel states revealed that the CT absorption is approximately 30 times stronger in the gel state compared to that in the solution state (see the Supporting Information, Figure S3).…”
mentioning
confidence: 99%